1970
DOI: 10.1039/j39700000285
|View full text |Cite
|
Sign up to set email alerts
|

Studies related to the chemistry of melanins. Part VI. Syntheses of 3-carboxypyrrole-2-acetic acid, 3,5-dicarboxypyrrole-2-acetic acid, and related compounds

Abstract: The acids named in the title weresynthesised. In the case of pyrroles already containing an ester group, a carboxylic function can be introduced by use of phosgene, but better by use of oxalyl chloride; an acetic ester group can be introduced by use of diazoacetic ester. Some pyrroles containing carboxy-or ester groups are N-methylated by diazomethane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1970
1970
1990
1990

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…(46,47) However, it has been found that the relative yields of pyrroles and furans produced by Benary's procedure (Table 3.2) depend upon the choice of amine. (45,)) It has been found that whereas an increase in the size of the groups R 1 , R 3 , and R 4 is detrimental to the formation of the pyrrole, large R 2 groups apparently aid the reaction.…”
Section: B59mentioning
confidence: 99%
“…(46,47) However, it has been found that the relative yields of pyrroles and furans produced by Benary's procedure (Table 3.2) depend upon the choice of amine. (45,)) It has been found that whereas an increase in the size of the groups R 1 , R 3 , and R 4 is detrimental to the formation of the pyrrole, large R 2 groups apparently aid the reaction.…”
Section: B59mentioning
confidence: 99%
“…(322) it would appear, however, from spectral evidence 091 * that the product from 3-acetyl-2,4-dimethylpyrrole is the 3-pyrryl(2,4-dioxobutyrate), (l90 ' 323) resulting from condensation of the acetyl group with diethyloxalate, and not the expected a-pyrrylglyoxylic ester. (327) Ethyl pyrroloylacetates, which have been reported to be the products of the reaction of substituted pyrrylmagnesium bromides with ethyl chloroformylacetate (318 ' 328) and by the Houben-Hoesch reaction of pyrroles with ethyl cyanoacetate, (329) are susceptible to cleavage to the acetylpyrroles under both acidic 091 ) and basic conditions. (B255) and (B256), which upon oxidation with sodium periodate cleave to give the formylpyrroles (B158) and (B257).…”
Section: O-/mentioning
confidence: 99%
“…Baseados nos estudos de melanogênese de Raper [Raper, 1928] e nos trabalhos de Swan e Waggott [Swan e Waggott, 1970], existem fortes evidências de que a 1 ,2,1ndolquinona (conhecida na literatura como 5,6,1ndolquinona) e suas formas reduzidas, semiquinona e hidroquinona, formam a maior parte do pigmento biologicamente ativo (Figura 1.1 ).…”
Section: Ntrod Ucãounclassified